Constitution of the alkaloid carpaine - Work, T. S. (The University of Edinburgh, 1936)
The constitution of the alkaloid carpaine is studied and a structure suggested containing a ten membered lactone ring. A possible method of synthesis in the plant is indicated,and a comparison of the heart depressor action of carpaine and carparimic acid is made.
The constitution of the alkaloid carpaine